Pembibitan dan Kultivasi Tanaman Pekarangan dengan Teknik Makropropagasi Sebagai Pembinaan Kelompok Tani Desa Suling Wetan Bondowoso - Mohammad Ubaidillah; Ika Purnamasari; Adhitya Wardhono; Ciplis Gema Qori’ah; Agung Nugroho Puspito; Mellfani Rhamadinda Nendra Tigara; Hasbi Mubarak Suud (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Social independence and alternative efforts to improve the village economy are joint or collaborative efforts through community service activities. The form of community service activities can be in the form of information transfer, education and technology or other planned activities. One of these fields can be agricultural activities, namely plant breeding or cell multiplication which functions to meet the need for seeds, especially for home gardens, ornamental plants, plantations, food and horticulture, all of which can be done independently for sale or to meet one's own needs. Cultivation of garden and horticultural crops in Suling Wetan Village still uses conventional methods which greatly affect overall production results. The macropropagation technique is an effort to obtain quality seeds that have viability, disease resistance and superior characteristics and are able to maintain the same characteristics as their parents. The service activities received a very good response from the Suling Wetan village farmer group and the general public. Farming groups or the general public can utilize macropropagation technology to support agricultural production at low costs and become an alternative source of income.